Application of the chocolate balloon (restrictive dilatation technique) in vascular preparation for arterial angioplasty of the lower limbs - Hongzhao, Zhong; Dawei, Zhang; Bo, Zhao; Xuesong, Yang; Huihan, Li; Qingzhi, Hao; Longyu, Song (Frontiers in Surgery, 2025)
ObjectiveThis study aims to compare the immediate clinical effects of the chocolate balloon and the conventional balloon in endovascular angioplasty of the lower limbs.MethodsClinical data were retrospectively collected from a single center, including 117 patients with lower limb arterial lesions treated from January to December 2021 and 112 patients treated from January to December 2023 at our center. The comparison focused on the incidence of vascular dissection after balloon dilatation, with secondary endpoints including the stent implantation rate.ResultsIn both groups, the success rate was 100%. Dissection formation rates in the chocolate balloon and conventional balloon groups were 20.5% vs. 17.5%, respectively. Non-flow-limiting dissection formation rates were 14.7% vs. 4.8% (P < 0.05), while severe dissection rates were 5.8% vs. 12.7% (P < 0.05). Stent implantation rates were 9.0% in the chocolate balloon group and 18.3% in the conventional balloon group (P < 0.05).ConclusionThe use of chocolate balloons resulted in a lower incidence of severe dissection and reduced the stent implantation rate compared to conventional balloons. It effectively prepares complex multiple lesions of lower limb arteries in real-world scenarios.